2018
DOI: 10.1016/j.ptsp.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Implications of knee crepitus to the overall clinical presentation of women with and without patellofemoral pain

Abstract: Kinesiophobia, catastrophism, knee stiffness, strength and physical function are all impaired in women with PFP, regardless of crepitus. In pain-free women, crepitus was associated with poorer objective function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…The step-down is considered an important objective function test for patients with PFP, since it mimics the function of stair descent, that is a common aggravating factor; besides that, Loudon et al 45 showed a high intrarater reliability for this measurement. De Oliveira Silva, et al 46 related that people with PFP present deficits in the number of step-downs compared to asymptomatic people. So, we recommend that the step-down test should be incorporated to all clinical assessments of people with PFP.…”
Section: Discussionmentioning
confidence: 99%
“…The step-down is considered an important objective function test for patients with PFP, since it mimics the function of stair descent, that is a common aggravating factor; besides that, Loudon et al 45 showed a high intrarater reliability for this measurement. De Oliveira Silva, et al 46 related that people with PFP present deficits in the number of step-downs compared to asymptomatic people. So, we recommend that the step-down test should be incorporated to all clinical assessments of people with PFP.…”
Section: Discussionmentioning
confidence: 99%
“…Knee crepitus is a common sign of young 10,11 and elderly individuals with knee pain as well as in asymptomatic individuals. 23 In most cases, the noise around the knee is physiological and is not associated with knee pain and physical function, as evidenced by our findings in a OA population and by a recent study with women with patellofemoral pain.…”
Section: Discussionmentioning
confidence: 99%
“…The same clinical test has been used in other studies. 10,11 The KL grade is a radiologic grading system for knee OA, which determines the severity of radiographic OA based of the presence and degree of osteophytes, jointspace narrowing (JSN), sclerosis, and deformity affecting the tibiofemoral joint, irrespective of clinical symptoms. KL defines OA in five grades (0 ---normal to 4 ---severe).…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were included if they presented anterior or retropatellar pain (1) corresponding to at least thirty on a 100-mm visual analog scale (VAS) in the previous week; (2) for at least 3 months; or (3) during at least two or more activities from prolonged sitting, squatting, kneeling, running, ascending and descending stairs, jumping, and landing. Exclusion criteria included a history of any lower limb surgery, history of patellar subluxation or dislocation, ligament or meniscus tears assessed clinically, presence of neurological diseases, or individuals who had received oral steroids and opiate treatment in the last month [ 28 ].…”
Section: Methodsmentioning
confidence: 99%